2000
DOI: 10.4278/0890-1171-14.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Educational Materials concerning Osteoporosis on Women's Knowledge, Beliefs, and Behavior

Abstract: These findings suggest that brief written educational materials can facilitate knowledge and belief change but that they do not promote behavior change. The generalizability of these findings is limited by the low study response rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…Providing written feedback about calcium intake increased calcium consumption in premenopausal women. 18 In a later study, Blalock et al found that when premenopausal women were given information tailored to calcium intakes, physical activity levels, and selected behavioral theory constructs they were more likely to consume adequate calcium than women who received only general osteoporosis information. 19 Using a meta-analysis, tailored written materials were effective in changing health behaviors if these interventions were informed by behavior and health behavior theoretical constructs.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Providing written feedback about calcium intake increased calcium consumption in premenopausal women. 18 In a later study, Blalock et al found that when premenopausal women were given information tailored to calcium intakes, physical activity levels, and selected behavioral theory constructs they were more likely to consume adequate calcium than women who received only general osteoporosis information. 19 Using a meta-analysis, tailored written materials were effective in changing health behaviors if these interventions were informed by behavior and health behavior theoretical constructs.…”
mentioning
confidence: 97%
“…Previous studies provide support for tailored messages based on health behavior theoretical constructs to increase calcium intake 18,19 and improve other healthy eating behaviors 22-24 than simply disseminating written material. Supplying written materials based on theory to target a particular population increased physical activity in health care workers 25 and women with multiple sclerosis.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Also, in the absence of a placebo control group that receives no active intervention, the ability to uncover the true effects of the mobile technology intervention was limited. However, other randomised-controlled trials that have used education alone have found no changes in lifestyle behaviours [16]: hence, we considered that the education group in our study provided a reasonable control for comparison with the mHealth group. We also had a small sample size which may have reduced the likelihood of our detecting significant differences in behaviours between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In Austria there are as yet no legal requirements with regard to enrichment with calcium or vitamin D. In the USA and Canada, for example, the enrichment of food products with vitamin D has been largely successfully implemented [42][43][44]. Numerous prevention studies show that awareness campaigns and exercise programmes with both children and adults, as well as older adults can bring about a change in lifestyle and subsequently promote bone health [45][46][47][48][49].…”
Section: Public Health Strategiesmentioning
confidence: 96%